1999
DOI: 10.1002/(sici)1099-0690(199911)1999:11<2757::aid-ejoc2757>3.3.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pressure on Retro Diels–Alder Reactions

Abstract: The activation and reaction volumes (∆V /∆V) were showing negative volumes of activation (∆V Ͻ 0) whereas the others are slightly retarded (∆V Ͼ 0). From the analysis determined for the retro Diels-Alder reactions of the parent dihydrobarrelene 1a, its 2-cyano derivative 1b, the exo and of the volume data including the van der Waals volumes (V w ) one can conclude that the packing coefficients of the endo Diels-Alder adducts of maleic anhydride to naphthalene exo-, endo-4, and the exo and endo Diels-Alder peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…In a more recent investigation F.-G. Klärner and V. Breitkopf observed that the retro Diels-Alder reactions of dihydrobarrelene and its 2-cyanoderivative and of the endo-DielsAlder adduct between dimethylfulvene and N-phenylmaleic imide are slightly decelerated by pressure showing positive volumes of activation whereas the retro Diels-Alder reactions of the endo and exo [4+2] cycloadducts between naphthalene and maleic anhydride and that of the exo adduct between dimethylfulvene and N-phenylmaleic imide are accelerated by pressure showing a negative volume of activation (Scheme 4) [25]. Grieger and Eckert [26] considered two explanations of the ratio Φ > 1 in the Diels-Alder reaction of isoprene with maleic anhydride: a larger dipole moment of the transition state or secondary orbital interactions which can only occur in endo Diels-Alder reactions.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…In a more recent investigation F.-G. Klärner and V. Breitkopf observed that the retro Diels-Alder reactions of dihydrobarrelene and its 2-cyanoderivative and of the endo-DielsAlder adduct between dimethylfulvene and N-phenylmaleic imide are slightly decelerated by pressure showing positive volumes of activation whereas the retro Diels-Alder reactions of the endo and exo [4+2] cycloadducts between naphthalene and maleic anhydride and that of the exo adduct between dimethylfulvene and N-phenylmaleic imide are accelerated by pressure showing a negative volume of activation (Scheme 4) [25]. Grieger and Eckert [26] considered two explanations of the ratio Φ > 1 in the Diels-Alder reaction of isoprene with maleic anhydride: a larger dipole moment of the transition state or secondary orbital interactions which can only occur in endo Diels-Alder reactions.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…12 The rate of the Diels-Alder reaction between substituted anthracenes and activated dienophile (7) NMR spectra differ significantly for the endo-and exo-adducts. 7 However, the NMR spectra of the adduct obtained in the catalyzed reaction 2 + 7 (Scheme 2) indicate the presence of the only one isomer (8 or 9). Exo-isomer 8 with m.p.…”
Section: 3mentioning
confidence: 99%
“…More drastic temperature conditions are unfavorable for the yield of the target adduct, because the process is reversible. Only elevated temperature (100 °C) and pressure (10-12 kbar) make it possible to achieve 90% yield of the product (adduct of naphthalene with maleic anhydride) 6,7 The purpose of this work was to estimate the reactivity of simple arenes as dienes in the Diels-Alder reaction, and to use different ways of activation of reactants in this reaction.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, innovative and unconventional synthetic procedures using water as solvent 1 under normal 2 and super heated conditions 3 , in supercritical fluids 4 , ionic liquids 5 and micro-emulsions 6 are being used now a days. Besides these, ultrasound 7 and microwaves 8 assisted reactions both in solvent as well as in solventless conditions are becoming popular due to their shorter reaction times and greater yields.…”
Section: Introductionmentioning
confidence: 99%